A Conceptual Model to Strengthen Integrated Management of HIV and NCDs among NIMART-Trained Nurses in Limpopo Province, South Africa - Nthuseni Sharon Murudi-Manganye; Lufuno Makhado; Leepile Alfred Sehularo (Clinics and Practice, 2023)
Integrated management of human immune deficiency virus (HIV) and non-communicable diseases (NCDs) in primary health care facilities remains a challenge. Despite research that has been conducted in South Africa, it is evident that in Limpopo Province there are slits in the implementation thereof. There is a need to develop a conceptual model to guide in strengthening the clinical competence of nurse-initiated management of antiretroviral therapy (NIMART)-trained nurses to implement the integrated management of HIV and NCDs to improve clinical outcomes of patients with the dual burden of diseases in Limpopo Province, South Africa. This study aimed to develop a conceptual model to strengthen the implementation of integrated management of HIV and NCDs amongst NIMART nurses to improve clinical outcomes of patients with the dual burden of communicable and non-communicable diseases in Limpopo Province, South Africa. An explanatory, sequential, mixed-methods research design was followed. Data were collected from patient records and the skills audit of 25 Primary Health Care (PHC) facilities and from 28 NIMART trained nurses. Donabedian’s structure process outcome model and Miller’s pyramid of clinical competence provided a foundation in the development of the conceptual model. The study revealed a need to develop a conceptual model to strengthen the implementation of integrated HIV and NCDs implementation in PHC, as evidenced by differences in the management of HIV and NCDs. Conclusion: The study findings were conceptualised to describe and develop a model needed to strengthen the implementation of integrated management of HIV and NCDs amongst NIMART nurses working in PHC facilities. The study was limited to Limpopo Province; the model must be implemented in conjunction with the available frameworks to achieve better clinical outcomes.